The productive landscape : wetland rehabilitation at the lower reaches of the Liesbeek River - Bhikha, Preetya (School of Architecture, Planning and Geomatics, 2014)
This dissertation explores the relationship between architecture, nature and the machine. It aims to investigate the potential for architecture to serve as a catalyst for site regeneration, specifically in a landscape that is undervalued in its current condition. The design, located at the lower reaches of the Liesbeek River, explores wetland rehabilitation and agricultural production, by viewing architecture as a soft machine that becomes a part of dynamic systems in ecological landscapes. The boundary has been selected as the means for architectural engagement, and the layers of the site are explored for their potential to create identity.The proposed programme comprises of an architecture of inhabited site works, that embodies the process of natural water filtration, using water from the Liesbeek River. Natural ecosystems are restored through the cultivation of endangered wetland plants in controlled growing beds for wetland rehabilitation on the site. Filtered water from the constructed wetlands is then used in hydroponic farming, supported by a water research facility. The conventional typology of landscapes of production is augmented through public interaction, which is facilitated through the provision of public amenities. These include a healthy-food café, public pool and change facilities, as well as a public wetland recreational park. The dissertation shows that through the creation of a productive landscape that facilitates public interaction, value can be given to an under appreciated site, by establishing identity through activation.